Alcohol and adolescents: study to implement municipal policies - Vieira, Denise Leite; Ribeiro, Marcelo; Romano, Marcos; Laranjeira, Ronaldo R (Revista de Saúde Pública, 2007)
OBJECTIVE: To build students' profile regarding alcohol consumption and risk behavior. METHODS: A total of 1,990 students were included in the study, aged 11 to 21 years old, from both genders, enrolled in public and private schools, in Southeastern Brazil, in 2004. A self-administered questionnaire was answered in the classroom without the presence of the teacher. The questionnaire also assessed the perception of how easy it was to get alcoholic beverages, the contexts where they drunk, and the consequences of drinking. RESULTS: Prevalence of lifetime alcohol use was 62.2%. Regarding consumption in the last 30 days, 17.3% of students reported at least one episode of binge drinking (five or more drinks). Adolescents reported that they had gotten alcoholic drinks very easily from shops, and also in social contexts with relatives and friends. Only 1% of underaged reported that they had tried and could not buy alcoholic beverages. As negative consequences of alcohol use in the last 12 months, students reported feeling sick due to drinking (17.9%), regret for doing something under the influence of alcohol (11%), blackouts (9.8%), and getting involved in a fight after drinking (5%). Over half of the students (55%) reported knowing someone who had been involved in a car accident because of a drunk driver. CONCLUSIONS: Data showed high prevalence of alcohol use among adolescents studied and how easy access to alcoholic beverages is, including to underaged people. Youngsters put themselves at risk and presented negative consequences of alcohol consumption. Prompt actions regarding public alcohol policies in Brazil are needed.